1986
DOI: 10.1007/bf00870987
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of bisoprolol with cimetidine and rifampicin

Abstract: In 6 healthy volunteers the pharmacokinetics of bisoprolol under steady-state conditions was investigated over three consecutive phases: over 7 days of 10 mg of bisoprolol once daily per os, 7 days of 10 mg of bisoprolol once daily plus 400 mg of cimetidine t.i.d. and 14 days of 10 mg of bisoprolol and 600 mg of rifampicin once daily with adequate intervals free of medication. After therapy with bisoprolol alone peak plasma levels (Cssmax) of the beta-blocker were 55.5 +/- 6.4 ng/ml (means +/- SEM), area under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
6

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 12 publications
1
21
0
6
Order By: Relevance
“…Investigations with bisoprolol in healthy volunteers have shown that about 50% of the drug is excreted unchanged by the kidneys and 50% is subjected to oxidative biotransformation (Kirch et al 1986;Leopold et al 1982Leopold et al , 1986. These findings have been confirmed by the results in the healthy subjects in this study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Investigations with bisoprolol in healthy volunteers have shown that about 50% of the drug is excreted unchanged by the kidneys and 50% is subjected to oxidative biotransformation (Kirch et al 1986;Leopold et al 1982Leopold et al , 1986. These findings have been confirmed by the results in the healthy subjects in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The data collected did not permit the calculation of the individual bioavailability fractions and the mean value of f was used. This procedure was assumed to be acceptable on the grounds that bisoprolol is a substance which is readily absorbed (> 90%), is subject to only a small first-pass effect (~ 10%), is not influenced by genetic oxidation polymorphism and which is insensitive to liver enzyme inhibition (Kirch et al 1986;Leopold et al 1986). Possible changes in bioavailability of bisoprolol caused by kidney or liver diseases should only be of minor degree.…”
Section: Glossary Of Phannacokinetic Symbolsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a therapy-fl'ee interval of 2 weeks, the crossover to the corresponding treatment phase, administering 600 mg rifampicin once daily or 150 mg vanitidine twice daily to the same patients orally for 7 days, was performed. In earlier studies it had been ascertained that 7 days of rifampicin therapy is sufficiently long enough to achieve the maxinmm enzyme-inducing effect of rifampicin [11]. Circadian blood pressure and heart rate were automatieally measured in all patients using the portable Pressurometer III (del Mar Avionics, Irving, CA, USA), which determined these values every half hour for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Only PRO in high dose showed a marked membrane activity [72]. After oral treatment, ATE significantly reduced blood pressure and heart rate in hypertensive patients but failed to inhibit 5-HT-induced platelet aggregation and 5-HT uptake by thrombocytes [116].…”
Section: Bab Drugs and Platelet 5-htmentioning
confidence: 98%